Effects of Gly71Arg mutation in UGT1A1 gene on neonatal hyperbilirubinemia: a systematic review and meta-analysis. (19th May 2019) - Mehrad-Majd, Hassan; Haerian, Monir Sadat; Akhtari, Javad; Ravanshad, Yalda; Azarfar, Anoush; Mamouri, Gholamali
Abstract: Objective: The associations between Gly71Arg polymorphism in the coding region of uridine diphosphate glucuronosyl transferase 1A1 (UGT1A1) gene and the risk of neonatal hyperbilirubinemia remained controversial. Therefore, a meta-analysis of observational studies has been conducted to assess the relationship between UGT1A1 gene polymorphism of Gly71Arg and neonatal hyperbilirubinemia susceptibility. Methods: An electronic literature search from online databases, such as PubMed, Embase, Cochrane, and Scopus was conducted to identify eligible studies. The effect summary odds ratio (OR) with 95% confidence interval (CI) was used to estimate the strength of association in the fixed or random effects model, based on the absence or presence of heterogeneity. Results: A total of 32 eligible studies involving 2634 cases of neonatal hyperbilirubinemia and 4996 controls were enrolled in this meta-analysis. The combined results showed that UGT1A1 Gly71Arg polymorphism was associated with an increased risk of neonatal hyperbilirubinemia in all genetic models (homozygote model: OR = 6.12, 95% CI = 4.42–8.46; heterozygote model: OR = 2.06, 95% CI = 1.82–2.33; dominant model: OR = 2.44, 95% CI = 2.03–2.93; recessive model: OR = 4.79, 95% CI = 3.48–6.59, and allelic model: OR = 2.37, 95% CI = 1.98–2.82). Subgroup analysis by ethnicity strongly validated this correlation in Asians but slightly in Caucasian population. Conclusions: This meta-analysis confirms that UGT1A1 Gly71Arg polymorphism significantly increases the risk of neonatal hyperbilirubinemia in Asian population, but results from the Caucasians were conflicting and further well-designed epidemiological studies are, therefore, required to more adequately assess this correlation.